2019
DOI: 10.17576/jkmjc-2019-3503-11
|View full text |Cite
|
Sign up to set email alerts
|

DVFx, and Modernization of Technology: Audience’s Changing Taste in the 21st Century

Abstract: The changes from analogue to digital in the film industry occurred rapidly and triggered a change in the landscape, especially in the usage of digital visual effects (DVFx). Thus, films that use the digital visual effects have developed a demand for technology exploitation among audiences. The most powerful effect afforded by digitization is the changes in the relationship between film and audience, especially in the aspect of cinema spectacle. Previously, the use of digital visual effects served merely to fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…When it comes to watching television, it is essential to have a conversation about one's cognitive and emotional requirements. The cognitive and emotional demands placed on respondents were found to have a substantial impact on how they accessed portal television, as stated by Hashim, (2019). They feel that watching television will fulfil both their intellectual and emotional requirements.…”
Section: Malaysian Youths Television Consumption Patternsmentioning
confidence: 91%
See 2 more Smart Citations
“…When it comes to watching television, it is essential to have a conversation about one's cognitive and emotional requirements. The cognitive and emotional demands placed on respondents were found to have a substantial impact on how they accessed portal television, as stated by Hashim, (2019). They feel that watching television will fulfil both their intellectual and emotional requirements.…”
Section: Malaysian Youths Television Consumption Patternsmentioning
confidence: 91%
“…According to research on audience segmentation, respondents are more likely to favour television programmes that are focused on personal interests rather than ones that are significant to them and their community. In addition, Hashim (2019) found that respondents' self-preferences and personal tastes had a substantial impact on the degree to which they enjoy watching television. There are significant differences between the gratification and satisfaction needs of viewers who are Malay and viewers who are not Malay when it comes to the portal television programmes that they choose to watch.…”
Section: Malaysian Youths Television Consumption Patternsmentioning
confidence: 99%
See 1 more Smart Citation